2022
DOI: 10.3389/fnagi.2022.793991
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Brain Structural Connectivity Networks and White Matter Integrity in Patients With Mild Cognitive Impairment

Abstract: White matter integrity and structural connectivity may be altered in mild cognitive impairment (MCI), and these changes may closely reflect decline in specific cognitive domains. Multi-shell diffusion data in healthy control (HC, n = 31) and mild cognitive impairment (MCI, n = 19) cohorts were downloaded from the ADNI3 database. The data were analyzed using an advanced approach to assess both white matter microstructural integrity and structural connectivity. Compared with HC, lower intracellular compartment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Extracellular amyloid protein deposition and intracellular neurofibrillary tangles are classic pathological hallmarks of Alzheimer’s disease ( Bergamino et al, 2022 ). An imbalance between the generation and degradation of Aβ protein leads to amyloid accumulation ( Cai et al, 2023 ).…”
Section: Pharmacological Effects Of Saponin Compoundsmentioning
confidence: 99%
“…Extracellular amyloid protein deposition and intracellular neurofibrillary tangles are classic pathological hallmarks of Alzheimer’s disease ( Bergamino et al, 2022 ). An imbalance between the generation and degradation of Aβ protein leads to amyloid accumulation ( Cai et al, 2023 ).…”
Section: Pharmacological Effects Of Saponin Compoundsmentioning
confidence: 99%
“…Combining dMRI and tractography enables the assessment of brain structural connectivity, which represents the WM tracts that physically interconnect brain regions in vivo ( 14 ). Additionally, tractography, in combination with graph theory, can been used to reconstruct and analyze the structural whole-brain connectivity in PD ( 10 , 15 ), as well as other neurodegenerative disorders ( 16 , 17 ). These studies in PD have revealed the existence of novel PD-specific anatomic networks, characterized by alterations in cortical–subcortical loops, reduced modular organization, and compensatory changes ( 15 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Convex Optimization Modelling for Microstructure Informed Tractography (COMMIT) (Daducci et al, 2015; Daducci et al, 2013) approach address this problem by deconvolving specific microstructural features on each streamline to recover individual contributions to the measured signal. By replacing the commonly used streamline count with intra-axonal signal fraction (IASF), it offers a quantitative and more biologically informative assessment of brain connectivity (Bergamino et al, 2022; Gabusi et al, 2022; Schiavi et al, 2022; Schiavi, Ocampo-Pineda, et al, 2020; Schiavi, Petracca, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…By replacing the commonly used streamline count with intra-axonal signal fraction (IASF), it offers a quantitative and more biologically informative assessment of brain connectivity (Bergamino et al, 2022;Gabusi et al, 2022;Schiavi et al, 2022;Schiavi, Ocampo-Pineda, et al, 2020;Schiavi, Petracca, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%